Functions of the Pointing Gesture in Mothers and Their 12 to 36 Month-old Children During Everyday Activities (2011)
ABSTRACT: This study longitudinally examined the production of pointing in four Spanish 1-year-old and four Spanish 2-year-old children in interactive situations with their mothers at home over the course of one year. Three aspects were analyzed: a) the functions of the pointing gesture, their accurate comprehension by the interlocutor (mother or child), and their order of emergence in the child; b) whether or not there were differences in the production of pointing according to who initiated the interaction; and c) whether maternal and child speech were related to maternal and child pointing production. The results showed that the pointing function of showing is the most frequent for both children and mothers from groups 1 and 2, and the first to emerge followed by the informing, requesting object, requesting action, and requesting cooperation functions. The accuracy with which these intentions were comprehended was found to be very high for both mother and child. Pointing production was greater when the speaker initiated the interaction than when the other person did, indicating that gestures follow the turn-taking system. Finally, the production of pointing to showing in children and mothers was found to be related to maternal and child speech, while pointing to request cooperation triggered the process of joint activity between mother and child.